Congenital diaphragmatic Bochdaleck hernia: Case report - Lava, Jamile Rizzardi; Hettwer, Guilherme A.; Reginatto, Cleiton Jonei; Galoro, Guilherme; Gehlen, Carolina T.; Subtil, Maria C.M.; Valenti, Vitor Engrácia [UNESP]; Deabreu, Luiz Carlos; De Mello Monteiro, Carlos Bandeira; Petenusso, Márcio (Springer Nature, 2012)
Congenital diaphragmatic Bochdaleck hernia is an anatomical defect of the diaphragm, which allows protrusion of abdominal viscera into the chest, causing serious pulmonary and cardiac complications in the neonate. In this study we aimed to present a case of congenital Bochdaleck hernia. We investigated a 40 weeks old child, with a pregnancy carried out in a public hospital in Passo Fundo, Rio Grande do Sul, Brazil. We suggest that if diagnosis occurs in the prenatal period, the prognosis of this disease improves. As a consequence, it allows the parity of the fetus to occur in a higher complexity center, optimizing the chances of survival. © 2012 Lava et al.; licensee BioMed Central Ltd.
Keywords: Diaphragmatic; Hernia; Infant; Newborn; Prenatal Care; acute kidney failure; Apgar score; atelectasis; blood testis barrier; case report; congenital diaphragm hernia; congenital diaphragmatic bochdaleck hernia; congenital heart disease; echocardiography; heart arrest; heart murmur; hernioplasty; human; lung insufficiency; male; neonatal respiratory distress syndrome; newborn; newborn intensive care; peritoneal dialysis; positive end expiratory pressure; resuscitation; thorax radiography; vaginal delivery; X ray